From Crisis to Specialty Coffee the Case of Nicaraguan Smallholder Cooperatives and Jesuit Business Education for Sustainability and Justice. - Le, Q.
Project-based service-learning has been proven to be an effective experiential learning opportunity that complements standard curricula in business schools. Seattle University (SU) has collaborated with its sister university, Universidad de Centro Americana (UCA) in Managua, Nicaragua, since 2015 on several project-based service-learning experiences focused on sustainable coffee farming practices and the implications that climate change may have on coffee farms and communities. This partnership with UCA and coffee cooperatives has its roots in the global coffee crisis of the early 2000s and has produced multiple projects that support farmers entering the specialty coffee markets. This paper as such presents the outcomes of our annual field research that took place in Penãs Blancas, Nicaragua in March 2018. Using the framework of sustainable coffee in light of environmental, social, and economic sustainability objectives, we provide evidence that many farmers in Nicaragua have been experiencing issues with their farms? sustainability. Our findings, moreover, reveal that the direct trade model used by the SU student-run social enterprise Café Ambiental is the most effective means of ensuring the farmers? economic sustainability, thereby allowing them to develop the environmental sustainability of their farms as well as improve their family and community health, education, and overall livelihoods for enhanced social sustainability. This social enterprise model created by SU students takes significant steps toward fulfilling the needs and improving the lives of coffee farmers in Nicaragua while preserving the land at the same time so future generations can grow quality coffee. Finally, we believe that our project has potential that is transferable to other Jesuit higher education institutions that utilize and pursue similar structures and objectives.